2020
DOI: 10.1007/s10265-020-01176-1
|View full text |Cite
|
Sign up to set email alerts
|

Tolerant mechanisms to O2 deficiency under submergence conditions in plants

Abstract: Wetland plants can tolerate long-term strict hypoxia and anoxic conditions and the subsequent re-oxidative stress compared to terrestrial plants. During O 2 deficiency, both wetland and terrestrial plants use NAD(P) + and ATP that are produced during ethanol fermentation, sucrose degradation, and major amino acid metabolisms. The oxidation of NADH by nonphosphorylating pathways in the mitochondrial respiratory chain is common in both terrestrial and wetland plants. As the wetland plants enhance and combine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 293 publications
(418 reference statements)
3
37
0
1
Order By: Relevance
“…Based on our result ( Figure 4 ) and previous reports, we have characterized the miR775- GALT9 module for its role in submergence stress response. Submergence stress causes oxygen-deprived conditions (hypoxia) (Nishiuchi et al ., 2012, Ahmed et al ., 2013, Chen et al ., 2015, Yeung et al ., 2018, Loreti and Striker, 2020, Nakamura and Noguchi, 2020). Hypoxic condition is the true consequence of submergence stress.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our result ( Figure 4 ) and previous reports, we have characterized the miR775- GALT9 module for its role in submergence stress response. Submergence stress causes oxygen-deprived conditions (hypoxia) (Nishiuchi et al ., 2012, Ahmed et al ., 2013, Chen et al ., 2015, Yeung et al ., 2018, Loreti and Striker, 2020, Nakamura and Noguchi, 2020). Hypoxic condition is the true consequence of submergence stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of leaf lactate abundance as a shading acclimation biomarker has not been indicated before, being a new contribution of the present study. Lactate is an oxidative stress related molecule ( Rivoal et al, 1991 ; Dolferus et al, 2008 ; Nakamura and Noguchi, 2020 ). While its root abundance has been associated with hypoxic conditions ( Dolferus et al, 2008 ; Maurino and Engqvist, 2015 ), the role of leaf lactate is not yet fully understood ( Maurino and Engqvist, 2015 ), having been associated mainly with the plant protection from pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Plant with low‐oxygen escape shows upward bending of leaves (hyponasty) that enhances shoot elongating and increased aerenchyma and gas films formation on the leaf surface, control radial loss of oxygen, induce the development of advantageous roots, pressurize gas flow through porous tissues and also modified the leaf and root anatomy (Blom, 1999; Jackson & Armstrong, 1999; Nakamura & Noguchi, 2020; Sauter, 2013). For instance, the deepwater verities of rice can escape from partially submerged conditions by increasing the genetic impression of SNORKEL1 and SNORKEL2 , which triggered the rapid internode elongation at the rate of 25 cm per day (Colmer et al., 2014; Hattori et al., 2011).…”
Section: Adaptation and Tolerance Mechanismsmentioning
confidence: 99%
“…Oxygen deficiency may significantly impact the growth and yield formation in these crop plants. Although several studies on plant responses to low oxygen are available (Fukao & Bailey‐Serres, 2004; Wiedenroth, 1993; Licausi, Van Dongen et al, 2010), nonetheless only a few studies reported the associated tolerance mechanism (Kato‐Noguchi, 2002; Mancuso & Marras, 2006; Mustroph & Albrecht, 2003; Nakamura & Noguchi, 2020). Two reviews on these interconnecting and interconverting stresses are available (Antonacci et al., 2007; Vartapetian et al., 2014); however, a comprehensive review addressing the plant responses and tolerance mechanisms to hypoxia and anoxia stresses is lacking.…”
Section: Introductionmentioning
confidence: 99%